Learning Chef a guide to configuration management and automation - Taylor, Mischa; Vargo, Seth (O'Reilly Media, 2015)
Get a hands-on introduction to the Chef, the configuration management tool for solving operations issues in enterprises large and small. Ideal for developers and sysadmins new to configuration management, this guide shows you to automate the packaging and delivery of applications in your infrastructure.